2021
DOI: 10.1111/ane.13418
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of epilepsy surgery candidates: A multicenter, machine learning study

Abstract: Objectives: Epilepsy surgery is underutilized. Automating the identification of potential surgical candidates may facilitate earlier intervention. Our objective was to develop site-specific machine learning (ML) algorithms to identify candidates before they undergo surgery. Materials & Methods:In this multicenter, retrospective, longitudinal cohort study, ML algorithms were trained on n-grams extracted from free-text neurology notes, EEG and MRI reports, visit codes, medications, procedures, laboratories, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Most of the included studies exploited NLP techniques to identify—and discriminate between—patients based on their documented clinical history and conditions 16–30 . The process often entailed classifying patient reports or interviews into predefined categories based on the prominent differences in textual features.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the included studies exploited NLP techniques to identify—and discriminate between—patients based on their documented clinical history and conditions 16–30 . The process often entailed classifying patient reports or interviews into predefined categories based on the prominent differences in textual features.…”
Section: Resultsmentioning
confidence: 99%
“…A series of research extended the applicability of NLP to identifying potential patient candidates for epilepsy surgery 21–24 . Wissel and colleagues validated the ability of a machine learning‐based NLP model to recognize various types of tokenized clinical features from EHRs, such as features describing seizure types and drug resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study revealed that AI-based models identified adult patients better than pediatrics eligible for surgery. However, it was possible to predict pediatric surgical patients 2.0 years before their presurgical evaluation (48). However, machine learning might not accurately predict long-term outcomes in some cases.…”
Section: Application In Surgical Management Of Epilepsymentioning
confidence: 99%